The Influence of Financial Factors on the Value of Non-Cyclical Consumer Companies on the Indonesia Stock Exchange - Hannifah Murtaaja Zulianti; Citra Ramayani; Dahen, Lovelly Dwinda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the effect of financial factors on firm value in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Specifically, the study investigates whether capital structure, liquidity, profitability, firm size, and dividend policy influence firm value. A quantitative research approach was employed using secondary data obtained from the annual reports of 30 companies selected through purposive sampling, resulting in 150 panel data observations. The data were analyzed using panel data regression with EViews 14. Based on the Chow and Hausman tests, the Fixed Effect Model (FEM) was selected as the most appropriate estimation model. The results indicate that capital structure has a positive and significant effect on firm value, while liquidity, profitability, firm size, and dividend policy do not have significant effects. In addition, all independent variables simultaneously have a significant effect on firm value. These findings provide empirical evidence on the determinants of firm value in the Consumer Non-Cyclicals sector and offer practical implications for investors and corporate managers in formulating financial and investment decisions.